Effects of farmyard manure, vermicompost and Trichoderma on flowering and corm attributes in gladiolus - Sisodia, Anjana; Singh, Anil K (Bangladesh Journal of Botany, 2018)
To see the effect of farmyard manure (FYM), vermicompost and Trichoderma alone and in combination on flowering and corm yield in gladiolus a field experiment was conducted. Application of vermicompost + Trichoderma resulted in early spike emergence, floret colour show, opening of first floret and increased diameter of first, third and fifth floret. Maximum length of spike, no. of florets/spike and duration of flowering was registered with application of farmyard manure. Treatment FYM + vermicompost significantly enhanced shelf life of first and third floret. However, maximum weight of corms/plant and diameter of corm recorded with FYM + vermicompost + Trichoderma and FYM + vermicompost treatments, respectively.